A Case of Klebsiella pneumoniae infection - Liu, Xuefang; Yu, Ning; Lu, Huaihai; Zhao, Yinlong; Zhu, Junyu; Liu, Ya (The Journal of Infection in Developing Countries, 2024)
Introduction: In recent years, hypervirulent Klebsiella pneumoniae (hvKp) has attracted increasing attention. It usually causes liver abscesses, which spread through the bloodstream to other parts such as the eyes, brain, lungs. 5.5% of all paroxysmal sympathetic hyperactivity syndrome are associated with infection, hydrocephalus, brain tumors, and some unknown causes. Younger patients with focal lesions of the brain parenchyma are at higher risk of paroxysmal sympathetic hyperactivity (PSH). Case presentation: This case report details the clinical features of Klebsiella pneumoniae diagnosed in a healthy individual. In addition to liver abscesses, bacteremia, and hyperglycemia, there are also brain abscesses, hernias, and postoperative paroxysmal sympathetic hyperactivity, an unexpected association between diseases or symptoms. The patient stabilized after comprehensive treatment, including early drainage of abscesses, rapid pathogen diagnosis, and timely and appropriate antibiotics. At a two-month follow-up, no signs of infection recurrence were noted, and the patient regained neurological function and could participate in regular physical activity. Discussion: Symptoms of Klebsiella pneumoniae infection usually appear gradually, and misdiagnosis is common. When young patients suddenly develop high fever and abscess at a particular site, Klebsiella pneumoniae infection should be considered routine. Paroxysmal sympathetic hyperactivity syndrome caused by infection is rare, but a clinical score (PSH assessment measure, PSH-AM score) should be performed when clinical features appear. Early diagnosis and treatment can improve the prognosis.